Auf Erfolgen aufbauend Zur Weiterentwicklung der Forschungsinfrastruktur für die Sozial-, Verhaltens- und Wirtschaftswissenschaft - Empfehlungen des Rates für Sozial- und Wirtschaftsdaten (RatSWD) - für Sozial- und Wirtschaftsdaten, Rat (Verlag Barbara Budrich, 2011)
This publication contains the recommendations of the German Data Forum (RatSWD) for expanding the research infrastructure for the social, economic and behavioral sciences. They were previously published as part of the comprehensive double-volume final report "Building on Progress - Expanding the Research Infrastructure for the Social, Economic, and Behavioral Sciences". The recommendations are based on the 68 advisory reports published in the aforementioned final report. They reflect the current status of consideration regarding design and development of an internationally viable and innovative research infrastructure for the social, economic and behavioral sciences in Germany. The information presented in this short volume is aimed at policy makers, researchers, as well as research sponsors.